A smart NIR fluorescent probe for the highly selective detection of palladium. Issue 11 (20th January 2017) - Tan, Hui-ya; Liu, Jing-gong; Zhou, Lin-fu; Li, Yu-kun; Yan, Jin-wu; Zhang, Lei
Abstract : A tailor-made colorimetric and NIR fluorescent probe for Pd 0 was developed by introducing allyl chloroformate into the methylene blue (MB) fluorophore. Abstract : A tailor-made colorimetric and NIR fluorescent probe for Pd 0 was developed by introducing allyl chloroformate into the methylene blue (MB) fluorophore. The probe exhibited vivid color change and significant fluorescence enhancement towards Pd 0, accompanied with excellent selectivity and sensitivity. No absorption and fluorescence response could be observed towards other metal ions. The fluorescence intensity of this probe showed a linear response to Pd 0 in the concentration range of 0–2 μM with a detection limit of 5.7 nM. Moreover, living cell imaging results indicated that this probe holds promising application prospects for detecting intracellular Pd 0 species based on its low cytotoxicity and specific turn-on NIR emission.